Harnessing student agency for easier transition and success: The role of life coaching (Journal of Student Affairs in Africa, 2023)
The use of life coaching as an intervention to support students in higher education has been explored in other contexts in the global north and evidence points to its possible benefits in improving student success and well-being. Although there is new emerging research on the use of life coaching in the South African higher education context, there is a lack of empirical evidence pointing to its benefits. We report some results from a longitudinal study that investigated the use of small group life coaching intervention to support students. The objective of the intervention was to harness first-year chemical engineering students’ agency by proactively equipping them with knowledge and skills that improve their studies and lives. Four years after the intervention, using Archer’s social realist concepts of structure and agency, we evaluated how the life coaching intervention influenced students’ agency during their studies. Data was gathered through one-on-one semi-structured interviews with ten students who had participated in the intervention during their first year and were currently in the fourth year of their studies. The results indicate that the life coaching intervention enabled students to mediate academic and non-academic constraints. Concerning academic constraints, the life coaching intervention helped students manage the transition from high school, including adjusting to a new workload, time management, learning to collaborate with their peers and dealing with experiences of failure. Concerning non-academic constraints, the life coaching intervention helped students clarify their goals, increased their self-awareness, deal with negative emotions, boosted their self-confidence, and become more resilient during the Covid-19 pandemic. We recommend more empirical research to be carried out in different contexts across higher education institutions in South Africa to explore further the possible role that life coaching may play in empowering students with life-long skills, reducing dropout rates and improving chances of success.
Keywords: Life coaching; student agency; student success; student support; engineering